Djibouti's Quest for Inclusive Growth - Kireyev, Alexei (IMF Working Papers; Working Paper ;, 2017)
The paper reviews Djibouti's macroeconomic reforms aimed at achieving middle-income status as envisaged in Vision Djibouti 2035, the authorities' development strategy. In this context, the paper reviews policy options available to the authorities in three critical reform areas: translating the investment boom into strong and inclusive growth to reduce poverty and unemployment; fiscal policy to support growth while preserving debt sustainability; and the important role of the business climate in growth acceleration.